Gunwale bobbing - Benham, GP; Devauchelle, O; Morris, S; Neufeld, J (American Physical Society, 2022)
We investigate gunwale bobbing, a phenomenon in which a person jumping on the gunwales of a canoe achieves horizontal propulsion by forcing it with vertical oscillations. The canoe moves forward by surfing the resulting wave field. After an initial transient, the canoe achieves a cruising velocity which satisfies a balance between the thrust generated from pushing downwards into the surface gradients of the wave field and the resistance due to a combination of profile drag and wave drag. By superposing the linear wave theories of Havelock [Proc. R. Soc. A 95, 354 (1919)] for steady cruising and Helmholtz for an oscillating source, we demonstrate that such a balance can be sustained. We calculate the optimal parameter values to achieve maximum canoe velocity. We compare our theoretical result to accelerometer data taken from an enthusiastic gunwale bobber and to estimates from videos of other canoeing aficionados. Finally, we discuss the similarities and differences with other examples of macroscopic wave-driven bodies and comment on possible applications to competitive sports.